An Overview of Cancer Biology, Staging, Metastasis, and Treatment Limitations - Rachaveti, Akhil (Asian Pacific Journal of Cancer Nursing, 2026)
Cancer represents a highly heterogeneous group of diseases driven by complex genetic, epigenetic, and microenvironmental interactions that result in diverse biological behavior and clinical outcomes. Despite substantial advances in molecular biology, diagnostics, and therapeutic strategies, cancer remains a leading cause of global morbidity and mortality, with advanced-stage disease continuing to pose major clinical challenges. This narrative review provides an integrated overview of fundamental cancer biology, including genetic alterations, hallmark capabilities, tumor microenvironmental influences, and intratumoral heterogeneity, alongside contemporary classification and staging systems. It examines the biological mechanisms and clinical consequences of metastasis, which remains the principal cause of cancer-related death, and reviews current treatment modalities such as surgery, radiotherapy, systemic chemotherapy, targeted therapy, hormonal therapy, immunotherapy, and emerging cellular therapies. The review critically discusses the major limitations of modern cancer treatment, including therapeutic resistance, treatment-related toxicity, immune escape, high cost, and latestage diagnosis. Particular emphasis is placed on understanding why metastatic (Stage IV) cancer remains largely incurable despite modern therapeutic advances, highlighting the roles of metastatic burden, microenvironmental protection, cellular dormancy, impaired drug delivery, and genetic instability. Finally, emerging future directions including precision oncology, oncolytic virotherapy, gene editing, nanomedicine, tumor vaccines, and liquid biopsy–based monitoring are explored as potential strategies to improve early detection, personalize treatment, and overcome resistance. This review aims to provide a cohesive, biologically informed synthesis to support more effective and personalized approaches to cancer care.